ANALISIS MUSIKALISASI PUISI SANG GURU MENURUT ESTETIKA IMMANUEL KANT DIKAITKAN DENGAN PENGALAMAN ESTETIS MAHASISWA [ANALYSIS OF THE MUSICALIZATION OF THE POEM SANG GURU ACCORDING TO IMMANUEL KANT’S AESTHETICS ASSOCIATED WITH THE AESTHETIC EXPERIENCE OF STUDENTS] - Laeli, Wardah; Syihabuddin; Yeti Heryati (Polyglot, 2025)
This research aims to describe the musicalization of the poem Sang Guru by Panji Sakti in Immanuel Kant’s aesthetic perspective and its relationship with students’ aesthetic experience. Poetry musicalization as a form of literary work that combines elements of music and poetry can also create a deep aesthetic experience for the audience. This research uses a qualitative approach by distributing questionnaires to 93 students to measure the aesthetic experience of the musicalization of the poem Sang Guru by Panji Sakti. The results showed 82.8% of students agreed that the musicalization of the poem Sang Guru by Panji Sakti was able to evoke aesthetic experiences. The aesthetic assessment of the musicalization of Sang Guru's poetry can be enjoyed universally. This is in accordance with the research results that as many as 62.4% of students agree and 37.6% of students strongly agree that the musicalization of Sang Guru's poetry has aesthetic value, so the musicalization of poetry can be said that its beauty is universal not subjective to individuals. Harmonization between poetry and music in the musicalization of Sang Guru's poem has an integration that weaves aesthetic value. Almost 99% of students agreed with this statement. The musicalization of the poem Sang Guru by Panji Sakti has a free aesthetic value without any practical purpose.  Abstrak bahasa Indonesia Penelitian ini bertujuan untuk mendeskripsikan musikalisasi puisi Sang Guru karya Panji Sakti dalam perspektif estetika Immanuel Kant dan hubungannya dengan pengalaman estetis mahasiswa. Musikalisasi puisi sebagai suatu bentuk karya sastra yang menggabungkan elemen musik dan puisi juga dapat menciptakan pengalaman estetis yang mendalam bagi penikmatnya. Penelitian ini mengunakan pendekatan kualitatif dengan menyebarkan angket kepada 93 mahasiswa untuk mengukur pengalaman estetis terhadap musikalisasi puisi Sang Guru karya Panji Sakti. Hasil penelitian menunjukkan 82,8% mahasiswa menyepakati bahwa musikalisasi puisi Sang Guru karya Panji Sakti mampu membangkitkan pengalaman estetis. Penilaian estetis terhadap musikalisasi puisi Sang Guru dapat dinikmati secara universal. Hal tersebut sesuai dengan hasil penelitian bahwa sebanyak 62,4% mahasiswa setuju dan 37,6% mahasiswa sangat setuju bahwa musikalisasi puisi Sang Guru memiliki nilai estetis, sehingga musikalisasi puisi tersebut bersifat universal bukan subjektif perorangan. Harmonisasi antara puisi dan musik dalam musikalisasi puisi Sang Guru memiliki keterpaduan yang menjalin nilai estetis. Hampir 99% mahasiswa menyepakati pernyataan tersebut. Musikalisasi puisi Sang Guru karya Panji Sakti memiliki nilai estetis yang bebas tanpa adanya tujuan praktis.